'Black holes': escaping the void. Issue 1 (28th January 2013) - Waldron, Sharn
Abstract: The 'black hole' is a metaphor for a reality in the psyche of many individuals who have experienced complex trauma in infancy and early childhood. The 'black hole' has been created by an absence of the object, the (m)other, so there is no internalized object, no (m)other in the psyche. Rather, there is a 'black hole' where the object should be, but the infant is drawn to it, trapped by it because of an intrinsic, instinctive need for a 'real object', an internalized (m)other. Without this, the infant cannot develop. It is only the presence of a real object that can generate the essential gravity necessary to draw the core of the self that is still in an undeveloped state from deep within the abyss. It is the moving towards a real object, a (m)other, that relativizes the absolute power of the black hole and begins a reformation of its essence within the psyche.